The Implications of Farm Production and Farmers' Characteristics on Poverty Reduction in Benue Division, Cameroon: A Multiple Correspondence Analysis Approach - Ntu, Sonkey Louis; Wonganya, Charlotte Nanyongo; Leonard, Kongnyu (Society & Sustainability, 2024)
The main objective of this study was to determine the effect of farm production and Farmers' Characteristics on Poverty Reduction in the Benue division in the Northern region of Cameroon. Data were collected from 399 respondents using a self-administered questionnaire through a stratified sampling technique of 12 sub-divisions in the Benue division. We adopted a survey research design. To estimate our results, we used Multiple correspondent analysis (MCA) and the OLS technique. The results reveal that there is a positive relationship between farm production and poverty reduction in Benue state. An increase in farm production will lead to a 2.19% reduction in farmers' poverty in Benue and this result is significant at a 5% level of significance. Similarly, the farmer's characteristics reveal that gender, farmers' experience, and educational level also significantly affect poverty reduction. In this light, there is a need for the government to train and deploy more extension workers in the various sub-divisions and communities in Benue division, to increase farmers' access to these services. This can be done by imparting specific skills to produce dominant food crops and livestock in the Benue division through workshops and seminars.